Use of Alternative Ways of Giving Evidence by Vulnerable Witnesses: Current Proposals, Issues and Challenges - Tinsley, Yvette; McDonald, Elisabeth (Victoria University of Wellington Law Review, 2011)
Fifteen years after the New Zealand Law Commission rejected pre-trial recording of cross-examination, that proposal is back on the reform agenda. Drawing from research examining comparative pre-trial and trial practices in cases of sexual offending, this article discusses the backdrop to the debate surrounding pre-recording, including the provisions of the Evidence Act 2006 and the approach of the courts to alternative ways of giving evidence. The benefits and drawbacks of pre-trial recording of evidence for adult witnesses are canvassed – including practical, evidential and psychological issues – leading to the conclusion that rather than a presumption in favour of any particular alternative way of giving evidence, close consideration of the individual circumstances of each case is required.